DOI: 10.11606/t.10.2014.tde-19092014-145052
|View full text |Cite
|
Sign up to set email alerts
|

Perfil bioquímico, metabolismo oxidativo e função de polimorfonucleares em equinos alimentados com óleo mineral, de soja, arroz, linhaça ou peixe

Abstract: RESUMO WEIGEL, R. A. Perfil bioquímico, metabolismo oxidativo e função de polimorfonucleares em equinos alimentados com óleo mineral, de soja, arroz, linhaça ou peixe. [Biochemical profile, oxidative metabolism and polymorphonuclear cells function of horses fed with mineral, soybean, ricebran, linseed or fish oils]. 2014. 59 f. Tese (Doutorado

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(41 reference statements)
1
1
0
Order By: Relevance
“…In the present study, it was shown that supplementation with a mixture of polyunsaturated oil, rich in omega 3, omega 6 and vitamin E, for a period of 8 weeks increased the concentration of SOD in the blood of horses under maintenance care and the concentrations of GPx, SOD and UrAc among the horses in training. It was also notable that the concentration of SOD was higher among animals under maintenance care (approximately 25% higher than animals in training) after 8 weeks, suggesting that exercise promotes a great imbalance in the free radical combat system, even among animals supplemented with antioxidant‐rich products, as previously reported in studies of athlete horses (Moffarts et al., ; Weigel, ).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…In the present study, it was shown that supplementation with a mixture of polyunsaturated oil, rich in omega 3, omega 6 and vitamin E, for a period of 8 weeks increased the concentration of SOD in the blood of horses under maintenance care and the concentrations of GPx, SOD and UrAc among the horses in training. It was also notable that the concentration of SOD was higher among animals under maintenance care (approximately 25% higher than animals in training) after 8 weeks, suggesting that exercise promotes a great imbalance in the free radical combat system, even among animals supplemented with antioxidant‐rich products, as previously reported in studies of athlete horses (Moffarts et al., ; Weigel, ).…”
Section: Resultssupporting
confidence: 67%
“…Weigel () demonstrated that horses supplemented with oil‐based diets (minerals, soy, linseed, fish and rice) did not exhibit differences in the concentrations of GPx and SOD in different treatment protocols (GPx: 231.63–346.33 UI/g; SOD: 1697.39–2125.54 U/g). In a study of Arabian horses submitted to exercise and supplementation (vitamin E), no differences were found between the control and supplemented groups in the pretest (~1080.0 UI/gHb) and post‐test (~1280.0 UI/gHb) assessments of the control animals or in the pretest (~1140.0 UI/gHb) and post‐test (1300.0 UI/gHb) assessments of the supplemented animals (Machado, ).…”
Section: Resultsmentioning
confidence: 99%